Identifikasi Golongan Senyawa Bioaktif Rhizophora sp. Di Perairan Pulau Morotai - Rinto M Nur; Nurmi Eso; Malka Rorano; Idham Suaibun (Universitas Musamus, Merauke, Papua, 2019)
Mangrove is a plant that lives in intertidal areas. Mangroves are generally used as building materials, boats and household utensils. However, at this time several types of mangroves have been developed and utilized as food ingredients, cosmetics, and medicines. This utilization is inseparable from the content of bioactive compounds contained in it. The aims of this research was to identify bioactive compounds of Rhizophora sp. at Pulau Morotai. The method used to obtain the extract was maceration using methanol. Qualitative identification of types of bioactive compounds using chemical detectors. Bioactive compounds identified include flavonoids, alkaloids, steroids, and saponins. The highest yield of methanol extract was obtained from bark (13,1%) with dark green extract color, followed by root extract (9,2%)with blackish yellow color and the lowest yield was found in methanol extract of leaf (2,7%) with blackish-green color. Bioactive compounds identified as Rhizophora sp. leaf samples contain bioactive compounds saponins and steroids. Bark contains bioactive compounds alkaloids, flavonoids, saponins and steroids, and roots contain bioactive compounds saponins and steroids.